Leviathisation or democracy? The case of post-war Bosnia and Herzegovina - Brljavac, Bedrudin (Dignitas (Ljubljana), 2011)
The main problem behind such democratic failures is that the emphasis in post-war Bosnia and Herzegovina was on a rapid democratisation process rather than building stable and fully functioning state institutions. The central argument has been that in the conditions of a serious institutional vacuum it is very difficult or almost impossible to carry out successful political and economic liberalisation reforms in post-war societies such as BiH.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; democratisation; demokratizacija; reforme; reforms; stabilne institucije; stable institutions